Design and Implementing of a Buck Dc-To-Dc Converter into the DC Motor's Speed Controller in Matlab/Simulink - keream, Settar (Anbar Journal of Engineering Sciences, 2022)
This paper presents a method for controlling the speed of a DC motor that is energized individually by utilizing a DC-DC Buck converter that is fed from a DC source. It can be easily controlled with the help of different types of DC-DC converters. This project was introduced a study and analyses of the buck DC to DC converter with PID controller cascaded with DC motors which is simulated in MATLAB. The required speed of the DC motor can then be obtained by giving a variable regulated voltage to the armature of the DC motor. A controller of the proportional-integral type is utilized so that the user can adjust both the amount of current flowing through the DC motor as well as the rate at which it rotates. These controllers allow for a quick control response. In addition to that, this paper presents a Simulink model for a DC motor that was created with Matlab Simulink. The purpose behind the development of the current and speed controller was to achieve stable and high-speed control of the DC motor. The final step is the display of the simulation results for the proposed system, which show that they are consistent with the expected results. This paper shown the DC motors was able to reach the necessary speed within a few attempts; however, as the load rose, the settling time increased as well.